2018
DOI: 10.1080/21645515.2018.1518843
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, understanding, attitude, perception and views on HPV infection and vaccination among health care students and professionals in Malaysia

Abstract: The human papilloma virus (HPV) is known to be a major causative agent of cervical cancers and warts, limited study has been conducted on its associated factors among health care students and professionals in Malaysia. The present study was carried to explore the knowledge, understanding, attitude, perception and views about HPV infection and vaccination. A total of 576 respondents were recruited to complete a self-administered questionnaire through convenience sampling across Malaysia. 80.% and of the females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Communitybased educational interventions are strongly needed, to improve parent's knowledge and attitude toward the government-sponsored vaccination program. 23,24 The concern of childhood vaccination is often testified as one of the hallmark attainment in public and child health promotion, despite this realization, the idea has been challenged particularly due to lack of awareness among mothers. This paper provides insight about mothers knowledge and attitude toward children's vaccination as the findings obtained may serve as the basis for effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Communitybased educational interventions are strongly needed, to improve parent's knowledge and attitude toward the government-sponsored vaccination program. 23,24 The concern of childhood vaccination is often testified as one of the hallmark attainment in public and child health promotion, despite this realization, the idea has been challenged particularly due to lack of awareness among mothers. This paper provides insight about mothers knowledge and attitude toward children's vaccination as the findings obtained may serve as the basis for effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The top three points of focus among knowledge, awareness, perception, attitude, and risky behaviors include knowledge ( n = 43), attitude ( n = 20), and risky behavior ( n = 17). Five focused on perception [ 1 , 10 , 11 , 12 , 13 ], and only two on awareness [ 14 , 15 ]. Questionnaire surveys ( n = 40) and interviews ( n = 29) were the two most popular methods used in data collection.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the sex profile, most of the studies reported females to have higher levels of knowledge, awareness, attitude, and perception compared to males ( n = 7). It is to noted however that a fair comparison is not possible, as many of these studies had a skewed distribution whereby females outnumbered males [ 10 , 40 , 43 ]. Additionally, some of these studies also specifically targeted female participants [ 1 , 14 , 39 ].…”
Section: Resultsmentioning
confidence: 99%